2017
DOI: 10.18632/oncotarget.17998
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a contributes to the PDGF-BB-induced phenotypic switch of vascular smooth muscle cells by suppressing Smad1

Abstract: The phenotypic switch of vascular smooth muscle cells (VSMCs) is a key event in the pathogenesis of various vascular diseases, such as atherosclerosis and post-angioplasty restenosis. Small non-coding microRNAs (miRNAs) have emerged as critical modulators of VSMC function. In the present study, miR-26a was significantly increased in cultured VSMCs stimulated by platelet-derived growth factor-BB (PDGF-BB) and in arteries with neointimal lesion formation. Moreover, we demonstrated that miR-26a regulates the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Endothelial and mural cells signal through several paracrine pathways to stabilize vessels including the PGFRβ, angiopoietin, TGFβ, and notch pathways to modulate cell-to-cell communication (Mack 2011;Winkler et al 2011).In one of the most important pathways for mural cell recruitment, endothelial cells release PDGF-BB ligands that acts on the mural cell receptor PDGFR-β to initially recruit vSMCs to blood vessels (Benjamin et al 1998;Lindahl et al 1997). There is evidence that miR26 is modulated by PDGF-BB signalling (Yang et al 2017). Yang et al, 2017, recently showed that neointimal hyperplasia results in elevated levels of PDGF-BB and is associated with upregulation of miR26 and the accumulation of vSMC at sites of injury, indicative of increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelial and mural cells signal through several paracrine pathways to stabilize vessels including the PGFRβ, angiopoietin, TGFβ, and notch pathways to modulate cell-to-cell communication (Mack 2011;Winkler et al 2011).In one of the most important pathways for mural cell recruitment, endothelial cells release PDGF-BB ligands that acts on the mural cell receptor PDGFR-β to initially recruit vSMCs to blood vessels (Benjamin et al 1998;Lindahl et al 1997). There is evidence that miR26 is modulated by PDGF-BB signalling (Yang et al 2017). Yang et al, 2017, recently showed that neointimal hyperplasia results in elevated levels of PDGF-BB and is associated with upregulation of miR26 and the accumulation of vSMC at sites of injury, indicative of increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that miR26 is modulated by PDGF-BB signalling (Yang et al 2017). Yang et al, 2017, recently showed that neointimal hyperplasia results in elevated levels of PDGF-BB and is associated with upregulation of miR26 and the accumulation of vSMC at sites of injury, indicative of increased proliferation. Furthermore, treatment of primary mouse aortic vSMCs with miR26a mimic drives cells to a synthetic vSMC state (Yang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies,it was shown that Smad1 protein expression was significantly decreased in balloon‐injured rat arteries and PDGF‐BB‐treated VSMCs. Anti‐miR‐26a attenuated the inhibitory effect of PDGF‐BB on Smad1 expression; Smad1 overexpression partially reversed PDGF‐BB inhibited differentiation markers in VSMCs, while Smad1 knockdown partially rescued phenotypic changes in VSMCs in cells transfected with anti‐miR‐26a (Yang et al, ). Thus, it was confirmed that miR‐26a had a regulatory effect on PDGF‐BB‐mediated Smad1 expression in VSMCs.…”
Section: Vsmc Proliferation Migration and Apoptosismentioning
confidence: 99%